ANALIZING THE FACTORS THAT DETERMINE CONSUMER PURCASE DECISIONS : THE EFFECTS OF PRICE PERCEPTION, BRAND IMAGE, AND WORD OF MOUTH AT KOPI KENANGAN MADIUN - Wahyuning Tias; Wahyu Prabawati Putri Handayani (LPPM STIE Muhammadiah Bandung, 2026)
The expansion of the coffee industry's market size in Indonesia is projected to continuously increase, resulting in the emergence of many coffee shops, one of which is the Kopi Kenangan brand. Kopi Kenangan is one of the favorite coffee shops for Indonesian people. In 2025, Kopi Kenangan reported operating more than 1,000 outlets domestically and 100 outlets abroad. This proves that Kopi Kenangan has penetrated the global market and become a favorite coffee shop with a strong brand image. In the second quarter of 2024, Kopi Kenangan experienced a sales increase of 27% contrasted to the previous year. This phenomenon reflects Kopi Kenangan's success in directly attracting consumer interest, thus influencing consumer purchase decisions. The objective of this study is to investigate the partial effect of price perception, brand image, and word of mouth (WOM) on the purchase decision at Kopi Kenangan Madiun Branch Outlet Cokroaminoto. This study employed a quantitative approach by sharing questionnaires to 100 respondents who meet the criteria of being at least 17 years old and having purchased Kopi Kenangan Outlet Cokroaminoto at least once. The data analysis method employed is purposive sampling. Data analysis was accomplished using multiple regression analysis and partial hypothesis testing (t-test) through SPSS version 20 software. The outcomes present a significant and positive partial effect of the variables price perception, brand image, and WOM on the purchase decision.